Local Economic Development Near The Austrian-Hungarian Border - Koroknai Hanna (2021)
The thesis covers the results of local economic development and regional cooperation be-tween Austria and Hungary, from the perspective of the Interreg V-A program, with special focus on the priority achievements of the program. These priorities include sustainability, environmental protection, mobility, competitiveness, and resource efficiency. These are derived from the benefits of regional cooperation. By including most of the historical mile-stones of the mutual ventures, the thesis has a strong background resource, that serves as the basis for the literature overview. The milestones include the end of the centrally-planned economy, the accession to the EU, the financial crisis in 2008 and the COVID-19 crisis. The original question of the research includes one’s understanding on the project part-ner’s motivation for participating in the project and identifying the main priorities of the Interreg programme. The citizen’s perceptions on the projects was a major question, if they have experienced positive or negative results. Analysing the barriers of the project execu-tion, acted as a tool for deepening one’s insight to answer the questions. The goals behind the research were the dedication of understanding the positive and negative effects of the programs and gathering information on why cooperation is a way to integrate regions and provide a immerse number of development opportunities. The applied methods to get information were the following: besides analysing the pe-riod of the Interreg program, more precisely the PaNaNet+ project through the report docu-mentations, a questionnaire was used to collect the citizen’s insights, opinions on their per-sonal benefits from the program. With an interview of the connector of the project part-ner’s, information was gathered on the regional motivations, the barriers, and the most im-portant inputs from all sides to achieve the programme’s goal. This input is trust, it was emphasized that no cooperation and partnership could survive a decade long joint venture without the pillars of trust, aid, and motivation to succeed as a community. Therefore, the most important conclusion the thesis is not on achieving more and more individual economic benefits but becoming a single entity, understanding the citizen’s needs, since they are the ones who contribute to the success and support the initiatives. No matter how well a project is structured, its worth’s nothing if the partners do not share the same views, they wish to succeed as one community and continue cooperating with one an-other in the future. Since the basic priority of the program is sustainability, the cooperation is expected to survive any kind of barriers, economic crisis, or halts. Therefore, it is unlikely to disappear in the next decade, but it is important to add, that throughout the years most of the ideas were concluded and executed. From this perspective, the lack of new ideas and the imple-mentation of all possibilities, represents the biggest problem for the future.